Development of Cold Formed Steel – Timber Composite for Roof Structures: Compression Members. (2015) - Awaludin, Ali; Rachmawati, Kundari; Aryati, Made; Danastri, Anindha Dyah
Abstract: The application of cold-formed steel on roof structures in Indonesia has become very popular in construction practices, especially for single- or multi-family dwellings. Compared to timber roof structures, cold-formed steel roof structures may require less or even no maintenance programs as they are absolutely durable against termite and wood-decay fungus attacks. However, lesson learned from recent building failures due to earthquakes indicated that cold-formed steel structures are susceptible to buckling failure. This study attempts to improve buckling performance of cold-formed steel members by combining them with timber laminas to obtain cold formed steel – timber composite. This composite member is obtained by attaching 15-mm thick timber laminas ( Swietenia mahagoni ) to the web part of cold-formed steel Z-, C-, and double C-sections using screws at regular spacing of 100 mm. Compression tests were conducted for five different effective lengths, and the increase in compressive load capacities of the composite members was validated by the results of compression test of cold formed steel (without timber laminas). The test results showed that the failure of composite members was progressive and it was initiated by flange local buckling followed by flexural buckling at the final stage. This failure mode is different from the observed common failure mode of the cold formed steel member which is instantaneous and is a combination of local buckling and flexural-torsional buckling. The increase in compressive load capacity was significant for short members but then decreases as the member length increases. A proposal to predict the compressive load capacity of cold formed steel – timber composite is presented for practical application.